2021
DOI: 10.21203/rs.3.rs-680796/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-COV-2 Seroprevalence among Health Care Workers in Private and Public Hospitals in Tehran, Iran

Abstract: BackgroundEstimating the prevalence of SARS-COV-2 antibody seropositivity among health care workers (HCWs) is crucial. In this study the seroprevalence of anti-SARS-COV-2 antibodies among HCWs of five hospitals of Tehran-Iran with high COVID-9 patient’s referrals was assessed.MethodsHCWs from public and private hospitals were included and were asked questions on their demographic characteristics, medical history, hospital role and usage of personal protective equipment (PPE). Seroprevalence was estimated on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There were six studies from the United States [10,12,19,24,25,31], six studies from India [16,18,20,27,29,32], two studies from the United Kingdom [17,26], two from Egypt [21,30], one each from Brazil [22], Chile [28], Ethiopia [33], Iran [15], Mexico [14], Qatar [11], Saudi Arabia [13] and Turkey [23].…”
Section: Figure 1 Prisma Flowchart Illustrating the Study Selection P...mentioning
confidence: 99%
See 1 more Smart Citation
“…There were six studies from the United States [10,12,19,24,25,31], six studies from India [16,18,20,27,29,32], two studies from the United Kingdom [17,26], two from Egypt [21,30], one each from Brazil [22], Chile [28], Ethiopia [33], Iran [15], Mexico [14], Qatar [11], Saudi Arabia [13] and Turkey [23].…”
Section: Figure 1 Prisma Flowchart Illustrating the Study Selection P...mentioning
confidence: 99%
“…The seroprevalence studies, with the exception of a single study from Iran [15], consistently reported that environmental services workers (housekeeping, cleaners and janitorial staff) were at a significantly elevated risk of having contracted COVID-19 compared to other healthcare workers in the same institution [10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28]. The quality of these cross-sectional studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal checklist for analytical cross-sectional study [34] by consensus among three study investigators (Q.X.N., C.Y.L.Y.…”
Section: Figure 1 Prisma Flowchart Illustrating the Study Selection P...mentioning
confidence: 99%